A passive acceleration sensor with mechanical 6 bit memory and mechanical analog-to-digital converter - Philip Schmitt; Martin Hoffmann (Micro and Nano Engineering, 2022)
This paper presents the design, modeling, fabrication and characterization of a passive micromechanical acceleration sensor intended for condition monitoring. The sensor is composed of purely micromechanical components forming a mechanical integrated sensing circuit, which allows to measure, select, store, and digitize the peak value of an imposed acceleration without the need of electrical auxiliary energy. We present micromechanical components arranged in a mechanical integrated sensor circuit. A network model is derived describing the static mechanical properties of the system. As part of the accelerometer, a cascaded mechanical memory is presented in detail which allows to store an acceleration peak value with a resolution of 6 bits, i.e. 64 discrete states. The memory is resettable by an electrostatic actuator. For an electrical read out of the memory, e.g. by RFID, an integrated micromechanical analog-to-digital converter is used.